2018
DOI: 10.1111/een.12509
|View full text |Cite
|
Sign up to set email alerts
|

Variation in composition of two bumble bee species across communities affects nectar robbing but maintains pollinator visitation rate to an alpine plant, Salvia przewalskii

Abstract: 1. In many flowering plants, bumble bees may forage as both pollinators and nectar robbers. This mixed foraging behaviour may be influenced by community context and consequently, potentially affect pollination of the focal plant.2. Salvia przewalskii is both pollinated and robbed exclusively by bumble bees. In the present study area, it was legitimately visited by two species of bumble bees with different tongue length, Bombus friseanus and Bombus religiosus, but it was only robbed by Bombus friseanus, the sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Flowering plants with long tubular flowers or nectar spurs are most likely to be robbed [46]. Previous studies reported that Salvia przewalskii was robbed by B. friseanus [29,30]. During our field collection, we also observed that Salvia leucantha was robbed by B. breviceps (Figure 2).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Flowering plants with long tubular flowers or nectar spurs are most likely to be robbed [46]. Previous studies reported that Salvia przewalskii was robbed by B. friseanus [29,30]. During our field collection, we also observed that Salvia leucantha was robbed by B. breviceps (Figure 2).…”
Section: Discussionmentioning
confidence: 50%
“…These two Asian bumblebee species are important pollinators for many plants and play key roles in local ecosystems. For instance, B. friseanus is an important pollinator for alpine plants, such as Pedicularis species [26][27][28] and Salvia przewalskii (Lamiaceae) [29,30]. B. breviceps is the major pollinator of Amomum subulatum [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are no dominant flowers for each node, and the development rate of each flower is inconsistent. Hermaphroditic flowers are self‐compatible and provide nectar as rewards for principal pollinator bumblebees (Ye et al, 2018). In general, anthesis usually starts with the two most basal flowers, but the following flowering order within the inflorescence is indistinct (Figure 1).…”
Section: Methodsmentioning
confidence: 99%